Investigation on frosting and defrosting performance of metal additively manufactured materials of different surface wettabilities - Muhammad Faisal Bin Abdul Manaf (Nanyang Technological University, 2023)
Frost formation is a major problem which affects industries such as aviation, appliance, transportation, and telecommunication. Therefore, this project studies and characterises the frosting and defrosting performance of additively manufactured (AM) aluminium (AlSi10Mg) and compare their performances with conventional aluminium alloy grade 6061 (Al6061). The tubes underwent surface treatment procedures to achieve different surface wettabilities, namely, superhydrophilic, superhydrophobic and slippery liquid infused porous surfaces (SLIPS). Frosting performance was evaluated at to two different relative humidity (RH) conditions, i.e., 40 % RH and 55 % RH, for three hours while keeping ambient temperature (20°C) and ethylene glycol-water mixture temperature through the tubes at -10°C. The defrosting performance was evaluated by allowing the tubes to defrost at ambient temperature (20 °C). The superhydrophobic AM tube had excellent performance with lower average frost thickness growth and surface area coverage. It effectively delayed full frost formation throughout the entire experiment, achieving < 100% surface area coverage. Additionally, the superhydrophobic Al6061 lost its superhydrophobic properties, achieving 100% surface area coverage under both RH conditions. SLIPS tubes also had a significant amount of full frost formation delay in the early stages of the experiment, but frost covered approximately 99% of the surface area by the end of the experiment. This delay was speculated to be caused by the lubricant increasing thermal resistance between the surface and water droplet. Superhydrophilic and untreated surfaces had a 100% surface area coverage in the early stages of the experiment, took the longest time to defrost.